2009
DOI: 10.1007/s00221-009-1899-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carnosine on long-term plasticity of medial perforant pathway/dentate gyrus synapses in urethane-anesthetized rats: an in vivo model

Abstract: The objective of this study was to examine the effect of carnosine on the hippocampal-dependent learning in perforant pathway/dentate gyrus synapses. The experiments were carried out on adult rats. A bipolar stimulating electrode was placed to the medial perforant path and a double-barrel glass micropipette was placed in the dentate gyrus as the recording electrode. Artificial cerebrospinal fluid (to control group) or carnosine (0.1, 1 microg/microL) was infused into the dentate gyrus via one of the barrels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Monophasic 10 V and 0.175-ms pulses were generated by the A/D board (Powerlab/8SP, ADInstruments, Colorado Springs, CO, USA) of a computer and triggered to a stimulator which was connected to an isolator (Suer et al, 2009). Biological signals were amplified (1000×).…”
Section: Methodsmentioning
confidence: 99%
“…Monophasic 10 V and 0.175-ms pulses were generated by the A/D board (Powerlab/8SP, ADInstruments, Colorado Springs, CO, USA) of a computer and triggered to a stimulator which was connected to an isolator (Suer et al, 2009). Biological signals were amplified (1000×).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to these glutamate regulators with a wide range of efficacy, the last two decades of neuropsychopharmacology research has concentrated on complementary and herbal medicine to develop more effective and less expensive therapeutic agents with safer side effect profiles for alleviating symptoms of mood and behavioral disorders ( 94 , 95 ). In an in-vivo experiment, Süer et al reported that L-carnosine might also play a role in synaptic plasticity ( 96 ). Multiple studies have revealed that the application of L-carnosine would be of benefit in neuropsychiatric disorders, including autism, schizophrenia, obsessive-compulsive disorder, attention-deficit hyperactivity disorder, major depression disorder, Alzheimer’s, and Parkinson’s diseases ( 97 , 98 ).…”
Section: Discussionmentioning
confidence: 99%